Comparison between Wright and Shukla formulas: which is better for the placement of umbilical catheters in newborns ≤ 1500 g? - Diana A. Castañeda-Pérez; Carolina Villegas-Álvarez; Adolfo San Román-Flores; Mauricio Pierdant-Pérez; Daniel Herbert-Anaya; Jorge G. Reyes-Vaca; Jorge F. Ayala-González; Francisco J. Escalante-Padrón (Boletín Médico del Hospital Infantil de México, 2023)
Background: Intravascular venous (VUC) or arterial (AUC) umbilical catheter placement is the most frequent invasive procedure in the neonatal intensive care unit (NICU). Either Wright’s or Shukla’s formula is used to introduce the catheters. However, Shukla’s formula is associated with incorrect insertion, especially for newborns < 1500 g. This study aimed to determine by chest X-ray if Wright’s formula is better than Shukla’s formula for the correct placement of umbilical catheters in newborns ≤ 1500 g. Methods: We included patients admitted to the NICU of a secondary-level hospital between 2021- 2022 who received VUC or AUC through the Wright or Shukla formulas. Results: A total of 129 newborns were included: 78 with VUC and 51 with AUC. In VUC, 50% with Wright and 36.8% with Shukla formulas had the correct location, (p = 0.24). In AUC, 56.6 % with Wright and 52.4% with Shukla formulas were placed correctly placed, (p = 0.76). VUC with weight < 1000 g were correctly placed in 36.4% with Wright and 33.3% with Shukla formulas (p = 0.58). VUC in newborns > 1000 g were correctly placed in 66.6% with Wright and 38.4% with Shukla formulas (p = 0.065). AUC in newborns < 1000 g were correctly placed in 45% using Wright and 42.9% Shukla formulas (p = 0.63). AUC in newborns > 1000 g were correctly placed in 80% using Wright and 57.1% Shukla formulas (p = 0.23). Conclusions: We found 13% more correctly placed VUC using Wright’s formula. Moreover, Wright’s formula was 29% above Shukla’s VUC placement in neonates > 1000 g, although there was no significant difference due to the sample size.